PENGARUH BITCOIN DAN EMAS TERHADAP HARGA SAHAM PERBANKAN YANG TERDAFTAR DI BEI - Yusril Rahman Hakim; Muchammad Rio Nugroho; Muhammad Hadyul Haq; Ladi Wajuba Perdini Fisabilillah; Tony Seno Aji (Jurnal Ekonomika : INDEPENDEN, 2025)
The banking sector plays a crucial role in Indonesia's economy, making it essential to investigate factors influencing banking stock prices. This study aims to analyze the impact of Bitcoin prices, gold prices, and BI Rate on banking stock prices listed on the Indonesia Stock Exchange from January 2022 to November 2024. The research employs a quantitative approach using panel data regression with a Random Effect Model (REM). The data used are secondary data sourced from Investing.com. The results indicate that Bitcoin prices and BI Rate have a positive and significant impact on banking stock prices, while gold prices show no significant effect. This implies that Bitcoin, as an alternative digital asset, increasingly affects financial market dynamics, whereas gold is more of a safe-haven asset with no direct correlation to banking stocks. The rising BI Rate reflects the positive performance of banking firms, thereby attracting investors' interest. This study provides insights into the roles of alternative investment instruments and monetary policy in shaping the dynamics of banking stock markets.